Determinants of Stress in Medical Practice: Evidence from Ontario Physicians - Campolieti, Michele; Hyatt, Douglas; Kralj, Boris (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
We use data from a unique survey of Ontario physicians to examine the determinants of work and personal stress in physicians with six stress indexes we constructed. We have a number of findings of particular interest. First, we find that males experience significantly less stress than women in a number of our regressions. Second, some of our estimates suggest that physicians who practice in health service organizations, which are paid primarily by capitation rather than fee-for-service, experience less stress. This estimate suggests that alternative payment systems, which are becoming more prevalent, may help to alleviate the stress experienced by physicians. Third, increases in the percentage of billings required to cover overhead expenses are associated with higher levels of stress. Finally, our most consistent empirical finding relates to the number of hours a week the physician works, which had a significant effect on all six of our stress indexes.